Accountability of the Bureau of Procurement Goods and Services of Banten Province in Implementing E-Procurement - Soebiandono, Soerjo; Ningrum, Sinta; Nurasa, Heru; Pancasilawan, Ramadhan (KnE Social Sciences, 2022)
Accountability is an important issue in scientific studies and in the field of public administration. Accountability in public organizations at the organizational level involves providing explanations to internal and external parties with an interest in evaluating the actions taken by these public organizations. The accountability of a public organization can be measured from several dimensions, including transparency, control, responsibility and responsiveness. A qualitative approach was used in this research. Data were collected through interviews and documentation studies, and descriptive data analysis techniques were used. The results showed that the implementation of e-procurement involved the principles of effective efficiency and open and non-discriminatory competition. Public accountability was also largely achieved. Keywords: accountability, organization, public, e-procurement